Spotlight on Leadership Path-Goal Theory Silos in Practice to Improve and Sustain Job-Oriented Development: Evidence from Education Sector - Atif Saleem (MDPI AG, 2021)
Sustainable development is a process occurring on several levels, which placed the expectations on educational institutions, especially secondary schools, change radically. Schools, therefore, are gradually likely to emphasize enhanced and sustainable teaching practices under the agenda of the United Nations 2030, sustainable future. Hence, the job-oriented development of teachers is a critical factor of the school leadership mechanism. Considering this, the present empirical research was designed to study the mechanism of path-goal theory (PGT) to sustain teachers’ job-oriented development in private secondary schools in Pakistan. The viewpoint of teachers, whose job performance is ultimately affected by the school leadership behavior and who perform the job at the front line in schools, was taken on board for the investigation. A total of 2469 secondary school teachers from 785 private secondary schools participated in the present study. Confirmatory factor analysis, t-test, Pearson correlation, and path analysis structural equation modeling analytics were mainly involved in the data analysis. Overall, the findings substantiated the constructive PGT mechanism, especially indicating that directive leadership is the most influential and effective leadership behavior in complex tasks, including when teachers are inexperienced. Moreover, the helpful role of supportive leadership and achievement-oriented leadership behaviors backs up the directive behavior. Although participative leadership behavior was problematic in the studied schools, it should be constructively adopted, as it was found to be a statistically significant predictor. Therefore, training programs for school leaders with good experience in participatory leadership functions can be productive for long-term teachers’ motivation. The literature shows that several secondary school teachers still perform poorly because of inadequate leadership, and the viewpoint of teachers on PGT was ignored in earlier studies. Hence, there was a dire need to conduct this research to address these concerns, especially in the non-Western, Asian context. In addition to pioneering academic research on leadership PGT in the secondary school context, the PGT elements were investigated, including teachers’ extrinsic and intrinsic motivation for the first time, adding new understanding about the theory.